Ebola Outbreak: An Evolving Epidemic- A Review - Kumar Patel, Vishnu; Patel, Umesh; Gedam, D. Sharad; Prasad Patel, Narmada; Verma, Jyotsna; Tiwari, Varsha (International Journal of Medical Research and Review, 2014)
Ebola hemorrhagic fever is a severe and often deadly illness that can occur in humans and primates (e.g. monkeys, gorillas). It is some of most virulent pathogens of humans, causing severe hemorrhagic fever that resembles fulminant septic shock. Recent outbreak of Ebola in West Africa has threatened the whole world, because of the high mortality (80-90%). No approved therapy is available for the treatment of these diseases, but progress has been made in new experimental approaches to post exposure prophylaxis and/or treatment that are effective in laboratory primates. Prevention is the best tool. Now WHO has also declared Ebola as a “public health emergency of international concern”. It can also be misused as a bioterrorism agent.